Advances in design and thermal systems select proceedings of ETDMMT 2020 - Ganippa, Lionel; Karthikeyan, R.; Muralidharan, V. (Singapore Springer, 2021)
The book presents the select peer-reviewed proceedings of the International Conference on Emerging Trends in Design, Manufacturing, Materials and Thermal Sciences (ETDMMT 2020). The contents focus on latest research in product design, CAD/CAE/CFD, robotic systems, neural networks, thermal systems, alternative fuels, propulsion systems, environmental issues related to combustion, autonomous vehicles and alternative energy applications. In addition, the book also covers recent advances in automotive engineering and aerospace technologies. Given the range of contents covered, this book can be useful for students, researchers as well as practicing engineers.
Structural and Thermal Analysis of Composite Wind Turbine Blade for Wind Mill Applications -- The Effect of Novel Cryogenic Treatment in the Microstructure AnalysisofAl 6101 Closed-Cell Foam -- Development of Toxic Gas Monitoring and Alarm System -- Predictive Modeling of Surface Roughness for Turning of Al-6061 Using Artificial Neural Network Model -- Microstructural evolution, phase formation and mechanical behaviour of Al 7017 alloy produced by Powder Metallurgy (P/M) technique.
Electronic reproduction
Keywords: Fluid mechanics; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Engineering design; Energy storage; Engineering Fluid Dynamics; Engineering Thermodynamics, Heat and Mass Transfer; Mechanical and Thermal Energy Storage; Electronic books